'Under the Thumb of the Party': The Limits of Tanzanian Socialism and the Decline of the Student Left. Issue 4 (3rd July 2020) - Melchiorre, Luke
Abstract : By late 1970, the University of Dar es Salaam had developed an international reputation as a leading centre of Third World socialist thought, with the emergence of a small, but increasingly influential, community of leftist students organising on campus. Over the course of the 1970s and 1980s, the prominence of this fledgling student left rapidly declined. Rejecting arguments which attribute this demise primarily to the university's growing material crisis during this period, this article argues that the introduction of a series of institutional reforms implemented by the TANU/CCM government over the course of the 1970s and 1980s on campus effectively institutionalised the ruling party's control over the university and its students. These institutional reforms ensured that, even as the ruling party's ideological hegemony began to wane as early as the late 1970s, the party was able to insulate itself from the kind of disruptive student protests that would undermine the stability of many of its African counterparts during the decade of the 1980s. Furthermore, this article demonstrates that the TANU/CCM regime's management of the university during these decades provides critical insights into some of the prime limitations of Tanzania's socialist project under Julius Nyerere: namely, that at the university, as elsewhere, the regime's need for political order and obedience from its citizens far exceeded, and often conflicted with, the ruling party's avowed desire to cultivate socialism among the Tanzanian masses.